Whole Genome Sequencing of Extended-Spectrum- and AmpC- β-Lactamase-Positive Enterobacterales Isolated From Spinach Production in Gauteng Province, South Africa - Richter, Loandi; du Plessis, Erika M.; Duvenage, Stacey; Allam, Mushal; Ismail, Arshad; Korsten, Lise (Frontiers in Microbiology, 2021)
The increasing occurrence of multidrug-resistant (MDR) extended-spectrum β-lactamase- (ESBL) and/or AmpC β-lactamase- (AmpC) producing Enterobacterales in irrigation water and associated irrigated fresh produce, represent risks related to environment, food safety and public health. In South Africa, information about the presence of ESBL/AmpC-producing Enterobacterales from non-clinical sources is limited, particularly in the water-plant-food interface. This study aimed to characterise 19 selected MDR ESBL/AmpC-producing Escherichia coli (n=3), Klebsiella pneumoniae (n=5), Serratia fonticola (n=10) and Salmonella enterica (n=1) isolates from spinach- and associated irrigation water samples from two commercial spinach production systems within South Africa, using whole genome sequencing. Antibiotic resistance genes potentially encoding resistance to eight different classes were present, with blaCTX-M-15 the dominant ESBL encoding gene and blaACT-types the dominant AmpC encoding gene detected. A greater number of resistance genes across more antibiotic classes were seen in all the K. pneumoniae strains, compared to the other genera tested. From one farm, blaCTX-M-15-positive K. pneumoniae strains of the same sequence type 985 (ST 985) were present in spinach at harvest and retail samples after processing, suggesting successful persistence of these MDR strains. In addition, ESBL-producing K. pneumoniae ST15, an emerging high-risk clone causing nosocomical outbreaks worldwide, was isolated from irrigation water. Known resistance plasmid replicon types of Enterobacterales including IncFIB, IncFIA, IncFII, IncB/O, and IncHI1B were observed in all strains following analysis with PlasmidFinder. However, blaCTX-M-15 was the only β-lactamase resistance gene associated with plasmids (IncFII and IncFIB) in K. pneumoniae (n=4) strains. In one E. coli and five K. pneumoniae strains, integron In191 were observed. Relevant similarity to human pathogens were predicted with PathogenFinder for all 19 strains, with a confidence of 0.635- 0.721 in S. fonticola, 0.852 – 0.931 in E. coli, 0.796 – 0.899 in K. pneumoniae and 0.939 in the S. enterica strain. The presence of MDR ESBL/AmpC-producing E. coli, K. pneumoniae, S. fonticola and S. enterica with similarities to human pathogens in the agricultural production systems reflects environmental and food contamination mediated by anthropogenic activities, contributing to the spread of antibiotic resistance genes.